The “Dark Is Hardworking” Association: How Skin Tone Affects Perceptions of Service Providers in India - Ghoshal, Tanuka; Gill, Tripat (Journal of Marketing Research, 2026)
Colorism, or discrimination based on skin tone, has been widely documented as privileging lighter and disadvantaging darker skin tones in personal and professional contexts. In contrast, the current research uncovers a novel and positive “dark is hardworking” association in India. This association is theorized based on sociological accounts linking dark skin to outdoor labor, personal accounts of dark skin–toned individuals overcoming discrimination to achieve success, and widespread media cues featuring dark skin–toned achievers in arduous career pursuits. Darker skin tone thus cues perceived competence of service providers, driven by perceptions of being more hardworking. Evidence from six studies, including five experiments and a behavioral field study, demonstrates that although lighter skin continues to be advantageous in attractiveness-favoring professions (such as beauty consulting), darker skin offers a distinct advantage to service providers in competence-favoring fields (such as financial and technical services). Furthermore, highlighting competence can increase the preference for darker skin–toned professionals, even in attractiveness-favoring domains. This research contributes to the literature on stigmatized groups, specifically colorism and its effects on stereotyped evaluation of service providers. The findings provide strategic insights for service providers and have implications for social policy.